Recomendações multidisciplinares portuguesas sobre o pedido de DXA e indicação de tratamento de prevenção das fraturas de fragilidade - Marques, Andréa (2016)
Objective: To establish Portuguese recommendations regarding the indications for ordering bone densitometry measurement to (DXA) and for starting treatment to prevent osteoporotic fractures. Methods: A multidisciplinary panel, representing a wide range of medical specialties and patient associations related to osteoporosis, as well as national experts in this field and in health economics, met to develop recommendations based on available evidence and expert consensus. Recently obtained data on the epidemiologic, economic and quality-of-life aspects of osteoporotic fractures in Portugal were used to support decisions. Results: Ten recommendations were developed covering the issues of indications for ordering DXA measurements and whom to treat with anti-fracture medications. Thresholds for assessment and intervention are based on the cost-effectiveness analysis of interventions at different thresholds of a ten-year probability of osteoporotic fractures, calculated with the Portuguese version of FRAX® (FRAX®Port), and taking into account Portuguese epidemiologic and economic data. Limitations of FRAX® are highlighted and guidance for appropriate adjustment is provided, when possible. Conclusions: Cost-effectiveness thresholds for DXA examination and drug intervention aiming at fragility fracture prevention are provided for the Portuguese population. These are practical, based on national epidemiological and economic data, evidence-based, and supported by a multidisciplinary panel of experts and scientific societies. Implementation of these recommendations has the possibility to assure the most effective use of health resources in the prevention of osteoporotic fractures in Portugal.